STUDENTS’ PERCEPTION OF USING DEEPL AS MACHINE TRANSLATION IN ENGLISH LEARNING - Munawwarah, Munirah; Martriwati (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2024)
Technological advances influence the development of educational support with various facilities offered to students such as DeepL as a translation machine that can be used as an alternative by students to understand English texts. This study aims to describe students' perceptions of the use of DeepL in English learning in Jabodetabek. The population of this study is 210 students who have had the experience of learning English by utilizing DeepL. This study is descriptive quantitative research using a questionnaire. In collecting data, this study used a 5-point Likert scale questionnaire to determine students' perceptions of the use of DeepL for learning English. The results of this study show that the mean of this study was over 3.5 reflecting good and very good perception. A total of 57.35% of students strongly agreed and 39.71% of students agreed that DeepL helps in understanding English texts, although the use of DeepL has impacts or drawbacks. DeepL helps students improve their vocabulary, and understanding of English and saves time in doing assignments, and students think that using DeepL to translate things or do assignments is ethical.